Uma canção para Ricardo - Mendes, Sandro Martins Costa (2015)
This study presents a full-length picture screenplay followed by its theoretical critical analysis. The screenplay depicts a main character, a teenager, who finds on the Internet some videos posted by his maternal grandfather, whom he had never met, since the grandfather had departed from the family several years before. After that, this teenager tries to establish a connection with his grandfather through recording and posting videos in response to his grandfather‟s videos. This sequence of events annoys the teenager‟s mother. However, when the teenager is about to finally meet his grandfather, the later falls into a coma. In the theoretical critical analysis part, I approach pertinent points in my screenplay, such as the memory (HUYSSEN, 2000; GAGNEBIN, 2009, BOSI, 2010), the resentment (KHEL, 2000, 2004), the issues concerning the visibility of people on the Internet (TISSERON, 2013; HÈNAFF, 2013), as well as the audiovisual importance in nowadays society (LIPOVETSKY e SERROY, 2010). On this part, I also discuss the Cinema (AUMONT, 2012; GAUDREAULT e JOST, 2009; DANCYGER, 2003), the screenplay as a media (COMPARATO, 1983; CAMPOS, 2007; CHION, 1998; CARRIEÈRE e BONITZER, 1998; FIELD, 2001) and the creative writing itself (OSTROWER,2010; BORDINI, 1991; ECO, 2013; PAMUK, 2011).